IMPLEMENTATION OF CURRICULUM 2013 AND ITS CHANGES TO PRIMARY AND SECONDARY EDUCATION IN INDONESIA - Mustabirin Alam (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2013)
Curriculum 2013 was implemented in 2013 with the target of schools is still limited and tiered, this target will be increased so that by 2015 all primary and secondary education apply it. The changes of KTSP 2006 to curriculum 2013 constituted a challenge due to the internal and external challenges faced by Indonesia. The curriculum change requires changes in national education standards, in this case the Graduation Competency Standards, Content Standard, Process Standard, and Assessment Standard. Curriculum 2013 demands graduate having a balanced attitude competencies, knowledge, and skills so that each subject in the curriculum of 2013 can not be separated from the core competencies achieved through learning with the scientific approach and assessed by means of authentic assessment